THE FORMULATION OF JACKFRUIT SEED FLOUR AND CASSAVA STARCH AS A FILLER IN SNAKEHEAD FISH (Channa striata) NUGGET - Selly Maulina; Maherawati Maherawati; Sulvi Purwayantie (Fakultas Pertanian Universitas Tanjungpura, 2020)
THE FORMULATION OF JACKFRUIT SEED FLOUR AND CASSAVA STARCH AS A FILLER IN SNAKEHEAD FISH (Channa striata) NUGGET Selly Maulina1), Maherawati2) dan Sulvi Purwayantie2)1) Student of Food Science and Technology 2) Lecturer of Agriculture Faculty Tanjungpura University*e-mail: selly123maulina@gmail.com AbstractNugget one of the popular food in Indonesia. The mayor of ingredients were meat or chicken protein mixed with wheat flour which is still import. West Kalimantan was the protein source located of snakehead fish that is still less consumed while the jackfruits seed was the waste that is still not optimally processed too. The aim of this research was to determine the formulation of jackfruit seed flour and cassava starch which produced chemical, physical and sensory characteristic of snakehead fish nugget. The research using Randomized Block Design of one factor (formulation of jackfruit seed flour and cassava starch) with five level treatments (0:20, 5:15, 10:10, 15:5, 20:0, w/w) and five replications. Data were analyzed by using one way ANOVA (α=5%) and if there was significant different followed by BNJ test (α=5%). Result showed that the best formulation based on effective index of snakehead fish nugget was jackfruit seed flour:cassava starch (10:10) that has moisture content of 52.25%; protein of 12.66% while as a albumin of 3.64%; fat of 4.45%; ash of 1.95%; carbohydrate of 28.70% and water holding capacity 51.6%. Meanwhile the hedonic result has taste 3.70 (quite like), flavor 3.53 (quite like) and texture 3.77 (quite like).Key words: flour, jackfruit seed, cassava starch, nugget, snakehead fish